Pengujian Berbagai Jenis Bahan Aktif Terhadap Penyakit Jamur Akar Putih (JAP) (Rigidoporus microporus (Swartz: Fr.)) di Areal Tanpa Olah Tanah (TOT) - Lydia Manurung; Lahmuddin Lubis; Marheni Marheni; Cici Indriani Dalimunthe (Jurnal Agroekoteknologi, 2015)
The objective of the research was to test of various types of active ingredient to White Root Disease(WRD) (Rigidoporus microporus (Swartz: Fr)) Without Tillage Area (WTA). This research wasconducted in the experimental garden of Sungei Putih, Deli Serdang with a height of ± 80 m aslfrom March 2014 until June 2014. The method used was Randomized Blok Design non factorial in3 replications. The factor was used active ingredients the pathogens aktif (triadimefon,Trichoderma sp, endophytic bacteria, bangun-bangun leaf extract, liquid smoke and water.Parameters observed were attack intensity, stem diameter and plant height. The results showed thatdifferent types of active ingredients very significant effect on the attack intensity and plant heightbut significant effect in stem diameter. The best result to suppress the intensity of theA (triadimefon) of 0% and C (endophytic bacteria) of 1.67%. The best result to increase in thediameter and plant height on B (Trichoderma sp) of 57.05% and 72.14%.Key words: active ingredients, Rigidoporus microporus, rubber, without tillage area